2006
DOI: 10.1002/elps.200500892
|View full text |Cite
|
Sign up to set email alerts
|

Neuroproteomics – the tasks lying ahead

Abstract: The brain is unquestionably the most fascinating organ. Despite tremendous progress, current knowledge falls short of being able to explain its function. An emerging approach toward improved understanding of the molecular mechanisms underlying brain function is neuroproteomics. Today's neuroscientists have access to a battery of versatile technologies both in transcriptomics and proteomics. The challenge is to choose the right strategy in order to generate new hypotheses on how the brain works. The goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 141 publications
0
21
0
2
Order By: Relevance
“…As shown in Figure 2, it is observable that especially the lateral parts of the gels show a lower resolution than the central parts which can lead to a possible misinterpretation of the regulation analysis of some protein spots. Therefore, it is possible to analyze a major part, but not the entire proteome of the Cx [36]. Additionally, it has to be mentioned that no analysis of enzyme activity was performed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…As shown in Figure 2, it is observable that especially the lateral parts of the gels show a lower resolution than the central parts which can lead to a possible misinterpretation of the regulation analysis of some protein spots. Therefore, it is possible to analyze a major part, but not the entire proteome of the Cx [36]. Additionally, it has to be mentioned that no analysis of enzyme activity was performed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous different histological regions, defined nuclei, subnuclei, and neuronal clusters can be distinguished, together with an immense number of connections and circuits. For many of these structures, specialized functions have been demonstrated that are reflected in the anatomical layout or molecular repertoire (Becker, Schindler, & Nothwang, 2006). Functional and structural heterogeneity continues on the cellular level.…”
Section: Complexity On the Structural And Functional Levelmentioning
confidence: 99%
“…The rapidly growing field of proteomics has excelled in several disciplines in biology, including injury, cancer, aging, and different neurological conditions, as well as psychiatric conditions including drug/substance abuse, schizophrenia, and depression (Abul-Husn and Devi, 2006;Becker et al, 2006;Becker, 2006;Choudhary and Grant, 2004;Cochran et al, 2003;Dean and Overall, 2007;Dumont et al, 2004). Proteomics is one of the fastest growing fields of biochemical sciences; a PubMed search reveals 287,021 articles published in the past 2 years containing the word ''protein,'' compared to 156,200 articles using the term ''gene'' ( January, 2011-April, 2013, which may also reflect a shift in genomics studies towards proteomics investigations.…”
Section: Challenges In Proteomicsmentioning
confidence: 99%